2010
DOI: 10.1007/s10900-010-9318-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Timing of Sex Education on Teenage Pregnancy in Nigeria: Cross-sectional Survey of Secondary School Students

Abstract: The objective of this study was to explore whether the time at which sex education was provided had any impact on reported cases of unintended pregnancies. A cross-sectional survey of secondary school students and their teachers was conducted using self-administered questionnaires. The participants were 1,234 students aged 14-17 years and 46 teachers in 5 secondary schools in South Eastern Nigeria. The outcome measures were reported pregnancies within the last 3 years by type of school and class level; class l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…In another study from Ghana, 74.6% of girls who were highly resilient to pregnancy cited their parents as a source of social support compared with 38.6% of low-resilience girls 36. Family instability, breakdown and parental divorce were cited as predictors in three of the studies 30 31 38. In a study in Ethiopia, respondents whose parents lived together had lesser odds of having sexual activities than those with divorced or separated parents 38.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In another study from Ghana, 74.6% of girls who were highly resilient to pregnancy cited their parents as a source of social support compared with 38.6% of low-resilience girls 36. Family instability, breakdown and parental divorce were cited as predictors in three of the studies 30 31 38. In a study in Ethiopia, respondents whose parents lived together had lesser odds of having sexual activities than those with divorced or separated parents 38.…”
Section: Resultsmentioning
confidence: 97%
“…In a South African study, lack of employment and job opportunities was found to be associated with teenage pregnancy 33. Sexual abuse and rape were cited as a predictor in three of the studies 29 31 32. In a Tanzanian study, girls reported rape as a cause for concern 29…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations